1995
DOI: 10.1152/jn.1995.73.4.1632
|View full text |Cite
|
Sign up to set email alerts
|

Rapid horizontal gaze movement in the monkey

Abstract: 1. We studied horizontal eye and head movements in three monkeys that were trained to direct their gaze (eye position in space) toward jumping targets while their heads were both fixed and free to rotate about a vertical axis. We considered all gaze movements that traveled > or = 80% of the distance to the new visual target. 2. The relative contributions and metrics of eye and head movements to the gaze shift varied considerably from animal to animal and even within animals. Head movements could be initiated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
124
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 0 publications
11
124
1
Order By: Relevance
“…This has been a controversial issue with respect to eye-head coordination during gaze shifts, and two general classes of models had been proposed to account for the available data: gaze feedback models (Tomlinson 1990;Galiana and Guitton, 1992;Goossens and Van Opstal, 1997) and separate feedback models (Phillips et al, 1995;Freedman, 2001;Sparks et al, 2002). In the first class of models, gaze accuracy is maintained by comparing the desired change in gaze position with the actual gaze displacement, which is calculated from feedback of the ongoing eye and head movements.…”
Section: Feedback and The Control Of Gaze Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been a controversial issue with respect to eye-head coordination during gaze shifts, and two general classes of models had been proposed to account for the available data: gaze feedback models (Tomlinson 1990;Galiana and Guitton, 1992;Goossens and Van Opstal, 1997) and separate feedback models (Phillips et al, 1995;Freedman, 2001;Sparks et al, 2002). In the first class of models, gaze accuracy is maintained by comparing the desired change in gaze position with the actual gaze displacement, which is calculated from feedback of the ongoing eye and head movements.…”
Section: Feedback and The Control Of Gaze Shiftsmentioning
confidence: 99%
“…Dynamic gaze feedback models incorporate this experimental result using their single feedback loop. Separate feedback models rely on either neck reflexes (Freedman, 2001;Freedman and Quessy, 2004;Quessy and Freedman, 2004) or, alternatively, the precise titration of the VOR (Phillips et al, 1995) to ensure gaze accuracy. Similarly, the results of single-unit recording experiments (Cullen et al, 1993;Cullen and Guitton, 1997;Phillips et al, 1999) have been used to support either class of model.…”
Section: Feedback and The Control Of Gaze Shiftsmentioning
confidence: 99%
“…Alternatively, Phillips et al (1995) suggested that the oculomotor system is independently driven by a saturated static gaze displacement command. Either way, since the eye may start at different positions in the orbit, the limitation of an oculocentric gaze displacement command does not, in general, prevent the eye from running against the bound aries o f the oculomotor range, unless the limits are ap propriately adjusted by taking eye position into account as well.…”
Section: Neurophysiologymentioning
confidence: 99%
“…In general, the saccadic eye and head components are temporally coupled (Freedman and Sparks 1997b;Phillips et al 1995;Zangemeister and Stark 1982a); the saccadic eye component initiates the gaze shift, and the onset of the head movement lags behind, at least in part, because of its heavier inertial load. When the initial eye-in-head position is deviated in the direction of the gaze shift (Becker and Jürgens 1992;Freedman and Sparks 1997b;Fuller 1996) or when the location and timing of the stimulus are predictable (Bizzi et al 1972;Moschner and Zangemeister 1993;Zangemeister and Stark 1982a,b), however, the lag in the head component can be reduced or it can even lead gaze onset.…”
Section: Introductionmentioning
confidence: 99%